The postcranial skeleton of the erythrosuchid archosauriform Garjainia prima from the Early Triassic of European Russia - Maidment, Susannah C. R. (2020)
Erythrosuchidae were large-bodied, quadrupedal, predatory archosauriforms that dominated the hypercarnivorous niche in the aftermath of the Permo-Triassic mass extinction. Garjainia, one of the oldest members of the clade, is known from the late Olenekian of European Russia. The holotype of Garjainia prima comprises a well-preserved skull, but highly incomplete postcranium. Recent taxonomic reappraisal demonstrates that material from a bone bed found close to the type locality, previously referred to as 'Vjushkovia triplicostata', is referable to G. prima. At least, seven individuals comprising cranial remains and virtually the entire postcranium are represented, and we describe this material in detail for the first time. An updated phylogenetic analysis confirms previous results that a monophyletic Garjainia is the sister taxon to a clade containing Erythrosuchus, Shansisuchus and Chalishevia. Muscle scars on many limb elements are clear, allowing reconstruction of the proximal locomotor musculature. We calculate the body mass of G. prima to have been 147-248 kg, similar to that of an adult male lion. Large body size in erythrosuchids may have been attained as part of a trend of increasing body size after the Permo-Triassic mass extinction and allowed erythrosuchids to become the dominant carnivores of the Early and Middle Triassic.